Analysis of Figurative Language and Imagery in Taylor Swift's Songs - Sari Rishita Siallagan; Sulastri Manurung; Juwita Boneka Sinaga (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
The aim of this research is to find out the kinds of figurative language and imagery in the song lyrics of Taylor Swift’s “1989” Album. Furthermore, in this research the researcher used qualitative descriptive method. The result of the study is presented in the form of paragraphs. The researcher analyzed the songs by reading them intensively and giving attention for each line. After that, the researcher examined the figurative language and imagery of the songs lyrics. After investigating the sentence in the songs lyrics, the researcher found eight kinds of figurative languages that are used in the songs lyrics, they are personification, metaphor, hyperbole, simile, oxymoron, allusion, litotes and metonymy. Six kinds of imagery also used in the songs lyrics, they are visual imagery, auditory imagery, organic imagery, kinesthetic imagery, tactile imagery and olfactory imagery. The most dominant of figurative language used is personification and the dominant imagery used is visual imagery. Keywords: figurative language, imagery, lyrics